Mujeres y políticas poblacionales: miradas desde Jalisco, México, en las décadas de 1920 a 1980 - Zoraya Melchor Barrera (Les Cahiers ALHIM)
This article analyzes the changes in the conception of women in population policies in Mexico and their impact in Jalisco between the 1920’s and 1980’s. The above is based on a review of the hemerography of the epoch and information derived from interviews with doctors and nurses. Post-revolutionary governments considered population growth and race improvement among their goals; the role of women was believed to be fundamental in the creation of the «new» State, being responsible for «procreating and training the future men of the nation». However, this conception was transformed from the 1960s, when women became the «object» of new family planning actions promoted in Mexico, but influenced by international organizations. This article proposes that the conception and work of women in population policies obeyed the interests of the State, first as the person in charge of providing the nation with its future citizens and, later, as the person in charge for reducing the growth of the population.